4D printing of shape memory polymers: from macro to micro - Spiegel, Christoph A.; Hackner, Maximilian; Bothe, Viktoria P.; Spatz, Joachim P.; Blasco, Eva (Advanced functional materials, 2022)
A novel and versatile shape memory ink system allowing 4D printing with light at the macroscale as well as the microscale is presented. Digital light processing (DLP) and direct laser writing (DLW) are selected as suitable 3D printing technologies to cover both regimes. First, a system based on monofunctional isobornyl acrylate and two crosslinkers consisting of a soft and a hard diacrylate is identified and proven to be compatible with both printing techniques. Employing DLP, a large variety of structures exhibiting distinct complexity is printed. These structures range from simple frames to more demanding 3D geometries such as double platform structures, infinity rings, or cubic grids. The shape memory effect is demonstrated for all the 3D geometries. Excellent shape fixity as well as recovery and repeatability is shown. Furthermore, the formulation is adapted for fast 4D printing at the microscale using DLW. Importantly, the 4D printed microstructures display remarkable shape memory properties. The possibility of trapping and releasing microobjects, such as microspheres, is ultimately demonstrated by designing, smart box-like 4D microstructures that can be thermally actuated—evidencing the versatility and potential of the reported system.
Online veröffentlicht: 6. Februar 2022
Gesehen am 13.03.2025